PENERAPAN TEAM ACCELERATED INSTRUCTIN (TAI) MENGGUNAKAN TUTOR SEBAYA DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV SD NEGERI 002 KEPENUHAN HULU PADA MATA PELAJARAN IPS - Sarman Sarman (STKIP Rokania Pasir Pangaraian, 2018)
This study aims to determine whether the learning model of Team Accelerated Instruction (TAI) using peer tutors can improve student learning outcomes on IPS subjects. The learning model of Team Accelerated Instruction (TAI) emphasizes that individuals who do not understand the material are the responsibility of other group members so that members who already understand need to provide assistance to members who do not understand. This TOD was conducted in the second semester of the academic year 2015/2016 for approximately three months starting from January 2016 to March 2016. The number of research subjects was 20 children with men as many as 14 people and women as many as 6 people. From the results of this study can be concluded that the use of Team Accelerated Instruction (TAI) can improve student learning outcomes in the subjects IPS class IV in SD Negeri 002 Kepenuhan Hulu T.A. 2015/2016 with an average learning result of 87.50. The average learning completeness of students is 90% with an increase of 65%. The average activity of students increased to 87.60 with good categories. The average research activity increased to 87.50 in the good category